Lemahnya Kontrol Sosial Pada Masyarakat Pedesaan (Studi Kasus Anak-Anak dan Remaja Kecanduan Menghisap Lem Aibon di Desa Suka Negeri, Kecamatan Topos-Kabupaten Lebong) - Citra Rafika (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This study aimed to identify and reveal the weakness of social control on rural communities, especially what happend to the children and adolescents who addicted to certain glue at the Desa Suka Negeri, Kecamatan Topos Kabupaten Lebong. This research was a qualitative with case study approach. The research data was collected by using involvement observation technique. In this study, researchers only passively involved in his observations. Researcher used in-depth interviews in order to get an idea of the lack of control social on rural communities. Especially what happend to the children and adolescents who addicted to certain glue in the village. The results showed that the deviation was the lack of vacancy control or social control. Every human being tend not to comply with the law or have the urge to have violated the law, it was seen in older people who spend more time in the plantion to meet the needs of their lives and let their children unattended, this condition force the children in that area to be involved in “ngelem” activity. This situation occured when their parents were in the plantion and did it together with other friends. The situation of rural communities that have a strong inner bound among the villagers and have equal responsibility for the safety and happiness, it made the village and a few citizens participate in conducting the social control, one of the way is by reprimanding the children and adolescents who caught “ngelem” activities and infrom it to their parents. But the existence of the village controllers mostly was not accepted by the parents, and they even got the threat from teenagers and children who did“the “ngelem” activity. On the other side, the merchants took part in the lack of the social control over these activities, many traders were not selective on their costumer who bought the aibon glue and some traders also let the children or teenagers to buy the aibon glue to get the profit.